Research on Thrust Allocation Strategy for ROVs Based on Constructive-Analytical Method - XU Lei; SONG Junhui; ZHANG Dinghua (Kongzhi Yu Xinxi Jishu)
This paper aims to solve the challenges related to complex and tedious thrust allocation calculations and the saturation of thrust output faced by remotely operated vehicles (ROV), based on a propulsion system model established for a specific type of miniature tracked electric ROVs. The resultant force (torque) was decomposed for each degree of freedom through an analytical method to derive the general expression of thrust output from each thruster. To address the saturation of thrust output, a constructive method was used to re-establish a functional relationship between the expected thrust (torque) output and the corresponding control voltage for each degree of freedom, taking into account the relative independence and coupling of expected thrust (torque) outputs among these degrees of freedom. Finally, the combination of the proposed constructive and analytical methods led to a new thrust allocation approach, which is called the constructive-analytical method. This method was compared with the conventional thrust allocation method—the pseudo inverse method—through simulations. The simulation results show that the constructive-analytical method not only simplifies the thrust allocation calculations but also effectively eliminates the problem of saturated output of thrust allocation.